Floodwater Nitrogen, Rice Yield and N Use Efficiency as Influenced by Deep Placement of Nitrogenous Fertilizers (Journal of Environmental Science and Natural Resources, 2015)
An experiment was conducted at the Soil Science Field Laboratory of Bangladesh Agricultural University, Mymensingh during the Aus season of 2012 to investigate the effects of deep placement of nitrogen (N) fertilizers on floodwater NH4-N concentration, rice yield and N use efficiency under alternate wetting and drying (AWD) condition. The experiment was laid out in a randomized complete block design with three replications. There were eight treatment combinations viz. T1 (Control), T2 [52 kg N from Urea super granule (USG)], T3 (104 kg N from USG), T4 [78 kg N from prilled urea (PU)], T5 (120 kg N from PU), T6 (51 kg N from NPK briquette), T7 (78 kg N from USG) and T8 (78 kg N from NPK briquette). The results regarding the floodwater NH4-N concentration revealed that, the highest value of (NH4M-N) was observed at the second day of PU application followed by gradual decrease with time. USG and NPK briquette treated plots showed negligible amounts of NH4-N in flood water during the sampling periods. The highest grain yield (5265 kg ha-1) and straw yield (6434 kg ha-1) was recorded from 104 kg N from USG (treatment T3) and the lowest values were obtained from control. Apparent nitrogen recovery by rice plants was much higher when 78 kg N was applied as USG. Nitrogen use efficiency decreased with the increase in N rate either as PU, USG and NPK briquette and treatment T7 (78 kg N as USG) showed the highest value. These results clearly indicate that the deep placement of N in the form of USG and NPK briquette minimizes the loss of N that results in higher N use efficiency and increased grain yield of rice as compared to broadcast application of N in the form of PU.DOI: http://dx.doi.org/10.3329/jesnr.v7i1.22173 J. Environ. Sci. & Natual Resources, 7(1): 207-213 2014